Anti-recipe as a component of composer’s creativity - Stronko, Boryslav (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2018)
Relevance of the study lies in highlighting the novelty impulse irreducible to clear algorithms as a truly creative component in composing music. The main objective of the study is to make fundamental delimitation between technical, stylistically- and historically-based component of composer’s thinking (recipe) and the moment of creative distancing from the already-known forms of thinking (anti-recipe), leading to new “recipes”. Methodology of the study. The comparative historical method applied to styles, composing techniques and situations of their change became the key method in the field of orchestration and changes in mode-tonal thinking in music of the 20th century. Combined with Claude E. Shannon’s notion of “information as a measure of the uncertainty”, this method revealed the moments of fundamental freeing from the inertia of previous forms of musical thinking. Key results and their significance. Besides the perception of a course of events in light of continuation of the previous in the subsequent, creative personalities have the ability to see the present in the reverse perspective, perceiving the past and the present as the launching ground for materialization of new opportunities. The inclination toward wilful break of inertia is evolutionally useful as boosting the thinking and its ability to flexibly respond to new challenges posed by the reality. The main paradoxes related to the anti-recipe are: 1) transformation of anti-recipe into a recipe of а new form of thinking; 2) change of anti-recipe’s social status from the carrier of non-conformism to the algorithm of social promotion after recognition of the appropriate personality (technique). Anti-recipe: the necessary setting of creative consciousness toward identification of conditionality and insufficiency of the existing music creation framework. Neither radical novelty of musical thinking nor the absence thereof nor the interim state could be self-sufficient for a substantial contribution to art. A free dialogue of an artist with both the entrenched tradition and its new forms is preferable.